ZikaMob – Influência das mídias sociais sobre a mudança de comportamento na prevenção de arboviroses - Albino, Victor Alves (2019)
The use of digital technologies and social media provides opportunities for developing and testing behavior change theories and techniques. The Feedback Intervention Theory advocates that social media likes can shape learning by acting as a reward mechanism in the brain, contributing to health behavior change. Currently, one of the main public health problems are arboviruses transmitted by the mosquito vector Aedes aegypti, which depends on the engagement of the population for its solution. In the first stage of this study, a review and quality assessment was carried out, using an internationally validated scale, of mobile applications aimed at preventing arboviruses in Brazil. In all, 29 applications aimed at dengue, zika and chikungunya prevention were analyzed; none of them had theoretical and methodological foundations in theories of behavior change. In the second stage, after the development of mobile-adapted software (ZikaMob), used during the educational intervention to disseminate actions and gather data on likes and shares of videos on social media, an investigation was conducted on the association between feedback. social media posts and behavior change. The design of this study was a quasi-experimental intervention involving 690 high school students from the state network of Campina Grande - PB. In all, 238 high school students from the city of Campina Grande, Northeast Brazil, produced and posted videos on Facebook and answered the self-reported questionnaire after the educational intervention. Of this group, 147 (61.8%) participants were female and 91 (38.2%) male, with a mean age of 16.61 ± 2.49 years. Approximately 70% received likes in their posts and 50% of them had their arbovirus prevention videos shared on social media. Most liked to post (76.1%) and saw the number of likes received (84%) and were more motivated to do the proposed activities as they received more likes (69.6%). There was an association between feeling motivated when receiving likes and performing preventive behaviors. However, receiving or disliking or sharing was not positively associated with the target behaviors of the educational intervention. The findings of this study showed that students who are more motivated with likes on social media perform more actions to prevent arboviruses. These findings may contribute to the planning of more effective educational interventions and actions using social media.